PERIPHERAL CHOROIDAL THICKNESS DETERMINED BY WIDE-FIELD OPTICAL COHERENCE TOMOGRAPHY IN EYES WITH CENTRAL SEROUS CHORIORETINOPATHY. Issue 8 (August 2022) - Nishihara, Soichiro; Maruko, Ichiro; Izumi, Takahiko; Kawano, Taizo; Iida, Tomohiro
Abstract : The choroid in eyes with central serous chorioretinopathy was thickened in the fovea and superior foveal area but not in the periphery in the wide-field optical coherence tomographic images. Abstract : Purpose: To determine the central and peripheral choroidal thickness in eyes with central serous chorioretinopathy (CSC) and to compare these thicknesses values with those of control normal eyes. Methods: Wide-field optical coherence tomographic images of 24 eyes of 19 patients with CSC and 14 normal eyes of 7 individuals were recorded. A 20-mm vertical scan through the fovea was obtained with the Xephilio optical coherence tomographic S1 (Canon, Japan), a wide-field optical coherence tomographic device. The subfoveal choroidal thickness and the thickness at 5 mm superior (S5) and inferior (I5), 7 mm superior (S7) and inferior (I7), 8.5 mm superior (S8) and inferior (I8), and 10 mm superior (S10) and inferior (I10) from the fovea in the CSC eyes and normal eyes were compared. Results: There was no significant difference in the age ( P = 0.8) or the refractive error ( P = 0.7) between the CSC and normal eyes. The choroidal thickness was significantly thicker in the eyes with CSC than that in the normal eyes at subfoveal choroidal thickness ( P < 0.01), S5 ( P = 0.01), and S7 ( P = 0.02). However, there was no significant difference in the choroidal thickness at the more peripheral points (all P > 0.1). Conclusion: The thickened choroid in CSC was observed at the fovea and the area just superior to the fovea. The pathogenesis of CSC may be associated with the choroidal thickening confined to the fovea and superior foveal area.